ANTIBACTERIAL ACTIVITY OF RED GINGER (Zingiber officinale var. rubrum) EXTRACTS AS GROWTH INHIBITORS OF Klebsiella pneumoniae - Rovik, Anwar (Universitas Karya Husada Semarang, 2024)
Pneumonia, a significant global health concern, is caused by Klebsiella pneumoniae infection. Antibiotic use is the primary treatment for K. pneumoniae infection; however, inappropriate use of antibiotics can result in bacterial resistance. Antimicrobial resistance poses a significant challenge in treating K. pneumoniae infections, as it can render existing antibiotics ineffective against infections. Natural products derived from plants have received considerable attention as potential sources of new antimicrobial agents, including red ginger (Zingiber officinale var rubrum). This study aims to determine red ginger extracts' effectiveness in inhibiting the growth of Klebsiella pneumoniae in vitro and silico. The research stages included compound extraction from red ginger rhizomes, antimicrobial activity testing against K. pneumoniae, and in silico analysis of target genes. The red ginger extract inhibited the growth of K. pneumoniae. The 25% extract concentration gave the most minor inhibition, with an inhibition zone of 6.7 mm. The 100% extract concentration gave the most significant inhibition, with an inhibition zone of 8 mm. The bioactive compound of red ginger may target various proteins and act in multiple sites in K. pneumoniae cells. This study showed that red ginger targets the acrR gene, a multidrug efflux pump AcrAB operon transcription repressor essential in the resistance of K. pneumoniae to antibiotics. Keywords: antimicrobial resistance; efflux pump; Klebsiella pneumoniae; red ginger Pneumonia masih menjadi masalah kesehatan global yang signifikan, disebabkan oleh infeksi Klebsiella pneumoniae. Penggunaan antibiotik adalah pengobatan utama untuk infeksi K. pneumoniae; namun, penggunaan antibiotik yang tidak tepat dapat menyebabkan resistensi bakteri. Resistensi antimikroba merupakan tantangan yang signifikan dalam mengobati infeksi K. pneumoniae, karena dapat membuat antibiotik yang ada menjadi tidak efektif melawan infeksi. Produk alami yang berasal dari tanaman telah mendapat perhatian yang cukup besar sebagai sumber potensial agen antimikroba baru, termasuk jahe merah (Zingiber officinale var rubrum). Penelitian ini bertujuan untuk mengetahui efektivitas ekstrak jahe merah dalam menghambat pertumbuhan Klebsiella pneumoniae in vitro dan in silico. Tahapan penelitian meliputi ekstraksi senyawa dari rimpang jahe merah, pengujian aktivitas antimikroba terhadap K. pneumoniae, dan analisis in silico gen target. Ekstrak jahe merah menghambat pertumbuhan K. pneumoniae. Konsentrasi ekstrak 25% memberikan daya hambat yang paling kecil, dengan zona hambat sebesar 6,7 mm. Konsentrasi ekstrak 100% memberikan daya hambat yang paling besar, dengan zona hambat sebesar 8 mm. Senyawa bioaktif jahe merah dapat menargetkan berbagai protein dan bekerja di berbagai tempat dalam sel K. pneumoniae. Hasil penelitian menunjukkan bahwa ekstrak jahe merah menargetkan gen acR, sebuah multidrug efflux pump AcrAB operon transcription repressor yang berperan penting dalam resistensi K. pneumoniae terhadap antibiotik. Kata kunci: jahe merah; Klebsiella pneumoniae; pompa eflux; resistensi antimikroba